Modern Thoraco-Lumbar Implants for Spinal Fusion (Springer International Publishing, 2018)
This book presents an updated perspective on spinal implants currently used in thoraco-lumbar spine surgery, leading to a rigid or dynamic spine fusion. The development of new surgical devices and techniques is mostly focused on a spinal fusion for lumbar instability due to trauma, tumours or degenerative or infectious diseases. Pedicle-screw fixation and fusion are currently considered to be the gold standard for most of the above-mentioned pathologies, and modern implants are designed to improve the accuracy of pedicle-screw placement and to allow the use of new surgical techniques and minimally invasive approaches. The content is relevant for surgeons, orthopaedic specialists, neurosurgeons, physiotherapists and osteopaths.